Carfilzomib-Induced Thrombotic Microangiopathy Treated with Eculizumab: A Case Report and Rapid Literature Review - Federica Pallotti; Claire Queffeulou; Mathieu Bellal; Bastien Jean-Jacques; Anne-Claire Gac; Valérie Chatelet; Annabel Boyer; Victor Gueutin (MDPI AG, 2022)
Background: Thrombotic microangiopathies (TMAs) can be induced by drugs. Recent works have indicated proteasome inhibitors, including carfilzomib, as a possible new causative agent. Although the physiopathology and management of carfilzomib-induced TMA are still unknown, eculizumab seems to be efficient. Results: We report a clinical case of TMA during carfilzomib treatment for multiple myeloma, possibly triggered by a concomitant influenza infection, suggesting a multi-hit process. Histologic analysis of the kidney biopsy proved renal TMA. Eculizumab allowed rapid and long-lasting renal and hematologic recovery. We enriched our work with a systemic review of published cases of carfilzomib-induced TMA treated by eculizumab. Twelve patients were included, all of whom presented acute renal failure and nine of them required hemodialysis. Eculizumab led to TMA resolution in eleven patients and complete renal recovery with hemodialysis withdrawal for seven of them within a month. One patient died from multiple myeloma progression. Two patients presented inter-current viral infection. Soluble complement fragment Bb and C5b9s were found in two patients and genetic benign variant of Factor H (CFH3-CFH1) in four. Conclusion: Our results suggest that eculizumab is effective in carfilzomib-induced TMA, which could support its inclusion as a treatment option. Further studies are required to clarify its physiopathology, complement role, and management.